A life sentence really? : the resettlement of ex-prisoners with a conviction for a sexual offence and the role of a housing support charity in this process /: the resettlement of ex-prisoners with a conviction for a sexual offence and the role of a housing support charity in this process. (March 2012) - Mills, Helen, 1980-; Dr, Grimshaw, Roger
No abstract available